Avaliação de sistemas agrivoltaicos na produção de culturas agrícolas - Silva, Felipe Marques da (2024)
The combination of photovoltaic systems and agricultural cultivation in the same location is referred to as agrivoltaic systems, providing a synergistic alternative for renewable energy generation and food production. Although this technology has been implemented in various commercial projects, its feasibility and impact on crop production have been underexplored. In this study, the implementation of agrivoltaic systems was assessed as an alternative for sustainable agricultural crop production in Brazil. The steps included a review of the state of the art of global agrivoltaics, highlighting advantages and barriers to its adoption. Additionally, suitable crops for this system were presented, along with guidelines for its implementation in agricultural areas. The research conducted a comparative economic evaluation of five distinct scenarios, encompassing exclusive lettuce cultivation, as well as the implementation of four different energy systems: a fixed-ground photovoltaic plant, a solar tracking photovoltaic plant, fixed-system agrivoltaics, and solar tracking agrivoltaics. The goal was to identify the investment costs for the systems, presenting values such as the Net Present Value (NPV), discounted payback period (DPP), and the Levelized Cost of Energy (LCOE). The main result obtained in the agrivoltaic research reveals an increase in revenue in the scenario with agrivoltaics in a fixed system, which demonstrated a cumulative NPV of R$ 2,360,038.78 and a DPP of 3 years, making it the most economically viable option due to its appropriate agrivoltaic architecture that benefited the developing crop.